Application of statistical methods in programming - Han, Zehua (London : ED-Tech Press, 2024)
Knowing and Using Basic Statistical Techniques R impressively overcomes any barrier that exists between analytical procedures and propels in quantifiable writing. The book presents current knowledge and advancements applicable to fundamental systems for managing non-ordinariness, exceptions, heteroscedasticity (unequal changes), and curvature, providing a theoretical foundation for understanding the relative advantages and uses of various strategies. The book uses R programming, which comes with a manual, to look into initial factual hypotheses and established techniques for addressing challenges using exemplary practises. The book includes classroom-tested sections that focus on either Rprogramming or computational topics to help the reader become noticeably familiar with core concepts and standards essential to understanding and using the various computational methods are now useable
Keywords: Statistical methods; Statistics; R programming